Study of therapeutic and prophylactic activity of complex herbal preparation "Immuvir" (Experimental biology, 2015)
Viral infections are still one and the main problems of humanity, threatening human health and life, as well as causing enormous economic damage . One way to solve this problem is the search for and development of fundamentally new, highly effective antiviral preparations.The aim of this work was the comparative study preventive and therapeutic activity of complex herbal preparation " Immuvir " and commercial drugs: ribavirin, geviran, rimantadine against influenza virus A/FPV/Rostock/34 strain in experiments on chickens.As a result of studies , it was found that the activity of the preparation "Immuvir" is comparable with therapeutic activity of preparation ribavirin and exceeds the therapeutic and prophylactic activity of geviran and rimantadine preparations.
Keywords: plant antiviral preparation; preventive; therapeutic activity